Mystery of Grass milk: A Deeper Dive into Quality, Quantity and Economics of Grass-milk in Dairy Cows - Md. Emran Hossain; Shilpi Islam (International Journal of Nutritions, 2025)
Consumers perceive ‘grass-fed milk’ as healthier than conventional ones since grass-fed milk contains higher levels of beneficial fatty acids and lower levels of omega-6. The study highlights the nutritional benefits of feeding green grass, in terms of quality, quantity, and farm economics emphasizing its specific influence on the fatty acid profile of milk, including enrichment of omega-3 fatty acids and conjugated linoleic acids. It also delves into the environmental benefits of green grass, for supporting sustainable agriculture and enhancing pasture development. It highlights the limitations in the current understanding of how green grass affects milk production efficiency and economic outcomes, prompting the need for a comprehensive investigation. The study aims to bridge these gaps by examining the intricate relationship between green grass utilization and its overall impact on the dairy farming ecosystem. The study further addresses the specific benefits of green grass for cattle promoting their health and welfare issues and contributing to environmental sustainability. Additionally, it contrasts the positive attributes of green grass with the potential drawbacks of feeding concentrate, which may lead to imbalances in nutrient intake, metabolic disorders, and various health issues of dairy cows. The study identifies reduced feed costs, lower dependence on purchased feeds, enhanced farm profitability, and improved feed conversion efficiency as the most economic advantages of green grass. The study, thus aims to advance knowledge and provide actionable insights for dairy farmers to optimize sustainability and efficiency in milk production by understanding specific mechanisms through which green grass influences milk yield and quality. Switching cows to grass and legume-based diets from concentrate will not only enhance the nutritional profile of milk but will also offer potential nutritional, environmental, and economic aspects of sustainable dairy development.
Keywords: Concentrate; Economics; Quality; Yield; grass; milk